Settlement of Regional Election Results Disputes: A Normative Analysis of the Provisions of Legislation in Indonesia: Settlement of Regional Election Results Disputes: A Normative Analysis of the Provisions of Legislation in Indonesia - Munir Rochmawanto; Fithriyatus Sholihah; Niswatun Faizah; Panji Dani Ramadhan (Universitas Islam Lamongan, 2025)
Regional Head Elections (Pilkada) are a crucial pillar of Indonesia's democratic system, manifesting popular sovereignty at the local level. Despite being a manifestation of democracy, Pilkada often gives rise to disputes that impact political stability and public trust. This study aims to examine the legal regulations and mechanisms for resolving disputes over the results of Regional Head Elections in Indonesia and identify challenges and solutions in their implementation. The research method used is normative juridical with a statutory approach. The results indicate that the Constitutional Court has the authority to handle disputes over the results of Regional Head Elections, while the Election Supervisory Agency (Bawaslu) and the State Administrative Court (PTUN) handle disputes over the process and state administration. However, implementation in the field faces challenges due to multiple interpretations of regulations, overlapping authority, and political pressure. Regulatory improvements, institutional strengthening, and legal education are needed to maintain the integrity of the Pilkada.